Environmental Responsibility and Policy in a Two Country Dynamic Input-Output Model - Rutger Hoekstra; Marco A. Janssen (Tinbergen Institute, 2002)
Increased spatial dependency of economic activities, as well as spatial differentiation of production and consumption, has implication for environmental policy. One of the issues that has gained importance is the responsibility for the emissions from products that cross national boundaries during its life cycle. This paper discusses the different ethical views of environmental responsibility. Furthermore, the policy measures that are associated with the different viewpoints on environmentally responsibility are analyzed in a novel dynamic two-country two-sector dynamic input-output model. A numerical example is used to illustrate that an ethically preferable tax, which takes account of environmental damages throughout the lifecycle of the product, is less effective that the current policy of taxing consumers of products. Therefore, we might conclude that policies that are based on ethically superior standpoints may have detrimental distortionary effects in the dynamic setting.
Keywords: 330; Dynamic input-output model; International trade; Technological change; Environmental responsibility; Environmental policy; Ethics.; Umweltpolitik; Ökosteuer; Internationale Wirtschaft; Input-Output-Analyse; Theorie